Medicine at theatre: a tool for well-being and health-care education - Tessa Marzi; C. Adembri; L. Vignozzi; B. Innocenti; M. A. Cruciata; D. Lippi (BMC Medical Education)
Abstract Effective communication plays a crucial role in healthcare settings, as it enhances patient outcomes and improves the overall quality of care and well-being. The rationale for this study was to use theater as a communicative tool by playing stories related to some important healthcare issues. The specific goal was to study the effectiveness of a specially designed theater intervention in enhancing psychological well-being and awareness of some aspects such as the doctor-patient relationships, communication skills, pro-social behavior, and empathy. A pre- and post-experience questionnaire was used to track the audience’s response. The results indicate that theater can efficiently promote well-being and spread crucial awareness about healthcare-related issues. Furthermore, the study underscores the varying perceptions and evaluations of health-related topics among individuals based on their age. Finally, we would like to underlie that theatre can also be a valuable tool for health communication. Clinical trial numberNot applicable.